Media barometer 1984 - Radio Sweden (Radio Sweden, 1998)
The first Media Barometer was conducted in 1979 and since then the survey has been carried out annually. The purpose is to explore how the Swedish population is using different media during an average day. In 1984 the respondents were asked if they had been doing any of the following the day before: watching video, listening to record player or tape recorder. If so, they were asked for how long period. They were also asked if the had been reading any of the following the day before: morning paper, evening paper, weekly magazine or any other magazine, or book. If so, they were asked how many and for how long period. Respondents answering that they did not read any weekly magazine or other magazine the day before were asked if they had been reading any during the last week. Book readers were also asked if they were reading the books for their own pleasure or if it was study literature. Furthermore respondents were asked about their radio listening habits. Background variables includes information on age, gender, education, occupation, and household composition.

Purpose:

Describe the trends and changes in people's use of mass media.

Mediebarometern genomfördes första gången 1979 och har sedan dess genomförts varje år. Undersökningen avser att belysa hur stor andel av den svenska befolkningen som en genomsnittlig dag tagit del av ett antal enskilda medier. Syftet är att beskriva tendenser och förändringar i människors utnyttjande av massmedier.

Syfte:

Beskriva tendenser och förändringar i människors nyttjande av massmedier.
Mediebarometern 1984
Keywords: newspaper readership; tidnings läsekrets; periodicals readership; tidskrifts läsekrets; listening to music; musiklyssnande; book use; bokanvändning; local broadcasting; lokalsändningar; households; hushåll; radio listening; radiolyssnande; reading (activity); läsande; Media; Media; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap